Synthesis and Characterization of Metal Modified Catalysts for Decomposition of Ibuprofen from Aqueous Solutions - Soudabeh Saeid; Matilda Kråkström; Pasi Tolvanen; Narendra Kumar; Kari Eränen; Markus Peurla; Jyri-Pekka Mikkola; Laurent Maël; Leif Kronberg; Patrik Eklund; Tapio Salmi (MDPI, 2022)
The presence of pharmaceuticals in surface water, drinking water, and wastewater has attracted significant concern because of the non-biodegradability, resistance, and toxicity of pharmaceutical compounds. The catalytic ozonation of an anti-inflammatory pharmaceutical, ibuprofen was investigated in this work. The reaction mixture was analyzed and measured by high-performance liquid chromatography (HPLC). Liquid chromatography-mass spectrometry (LC-MS) was used for the quantification of by-products during the catalytic ozonation process. Ibuprofen was degraded by ozonation under optimized conditions within 1 h. However, some intermediate oxidation products were detected during the ibuprofen ozonation process that were more resistant than the parent compound. To optimize the process, nine heterogeneous catalysts were synthesized using different preparation methods and used with ozone to degrade the ibuprofen dissolved in aqueous solution. The aim of using several catalysts was to reveal the effect of various catalyst preparation methods on the degradation of ibuprofen as well as the formation and elimination of by-products. Furthermore, the goal was to reveal the influence of various support structures and different metals such as Pd-, Fe-, Ni-, metal particle size, and metal dispersion in ozone degradation. Most of the catalysts improved the elimination kinetics of the by-products. Among these catalysts, Cu-H-Beta-150-DP synthesized by the deposition-precipitation process showed the highest decomposition rate. The regenerated Cu-H-Beta-150-DP catalyst preserved the catalytic activity to that of the fresh catalyst. The catalyst characterization methods applied in this work included nitrogen adsorption-desorption, scanning electron microscopy, transmission electron microscopy, and Fourier-transform infrared spectroscopy. The large pore volume and small metal particle size contributed to the improved catalytic activity.